Pelestarian Budaya Berkelanjutan: Internasionalisasi Tradisi Ruwatan Bumi di Candi Borobudur Melalui Bahan Ajar BIPA - Dian Maharani; Erlina Kusumastuti; Rizky Tzara Mufidah; Salma Fauziah Raudatul Jannah; Kundharu Saddhono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to explore the culture in the form of the Ruwatan tradition that developed around the Borobudur Temple area and used as teaching material for English for Foreign Speakers (BIPA). By using a literature study method that analyzes and synthesizes information from various relevant literature sources to be presented in descriptive-analytical form. The results show that by linking language learning with the Ruwatan tradition, foreign students not only learn Indonesian, but also gain an understanding of the symbolism, local wisdom, and spiritual perspectives contained in Indonesian culture.